IgG levels in Human Papillomavirus Infection Associated with Clinical Stage of Head and Neck Squamous Cell Carcinoma - Yussy Afriani Dewi; Agung Dinasti Permana; Fanny Yudhiono (Althea Medical Journal, 2021)
Background: Head and neck squamous cell carcinoma (HNSCC) is an invasive neoplasm of epithelial tissue in the head and neck and one of the etiologies of HNSCC is human papillomavirus (HPV) which maybe associated with the clinical stage of HNSCC. HPV infection in squamous cell epithelium produces specific IgG antibodies against HPV. IgG titer of HPV can help identify patients who are at risk for HPV-related cancers. This study aimed to explore the association between IgG titer of HPV with the clinical stages of HNSCC.Methods: The design of this study was analytic cross sectional, conducted at the Outpatient Clinic of Otorhinolaryngology-Head and Neck Surgery, Division of Oncology, Dr. Hasan Sadikin General Hospital Bandung period September-December 2017. Patients with HNSCC were recruited, and history was taken. Furthermore, histopathologic examination and HPV IgG serology examination was performed using the ELISA method. The HPV IgG levels were compared by stage and data were analyzed using the Shapiro Wilks test and Unpaired T test.Result: The HPV IgG was high in 75% (n=21) of HNSCC patients in the advanced stage and low in 25% (n=7) of patients in the early stage. There was  a significant relationship between HPV IgG titer and early and advanced stage of  HNSCC (p=0.001).Conclusion: The HPV IgG titer is related to the clinical stage of HNSCC indicating that the higher the HPV IgG level, the more advanced the clinical stage. Further study is needed to explore HPV IgG levels as a prognostic marker in HNSCC.